A modified fly ash-based mining filling material and its preparation method and application
By combining modified fly ash with lime, gypsum, sodium sulfate and other materials, combined with the use of epoxy resin, the problem of insufficient performance of mineral filling materials in extreme environments is solved, and the stability and strength of the material are improved under high and low temperature conditions.
Patent Information
- Application Number
- CN202411341930.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Mineral filling materials lack performance in extreme environments, especially in high and low temperature conditions, the stability and durability of the material are difficult to guarantee.
Modified fly ash is used as the base material, lime, gypsum, and sodium sulfate are used as the composite exciter, and epoxy resin is added to improve the dispersion and activity of fly ash through specific modification treatment methods, thereby enhancing the stability and strength of the filling material.
In high and low temperature environments, modified fly ash-based mineral filling materials can maintain excellent filling effect and long-term stability, significantly improve the compressive strength and durability of the material, and are suitable for mine filling.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mining filling, and in particular to a modified fly ash-based mining filling material and a preparation method and application thereof. Background Art
[0002] As an industrial byproduct, the application of fly ash in mine filling materials can bring economic benefits and environmental friendliness, but it also faces some challenges and shortcomings, mainly including: 1) Insufficient early strength: Fly ash-based filling materials usually have low strength in the early stage, which may affect the control of stratum subsidence and the stability of the filling body. 2) Large deformability: During the hardening process, fly ash paste filling materials may produce large deformations, increasing the risk of surface subsidence or instability of the goaf. Studies have shown that although the strength and elastic modulus of fly ash paste filling materials increase over time, the early strength is still insufficient. 3) Dispersion problem: The poor dispersion of fly ash in the filling material may affect its uniformity and filling effect during the filling process. Through modification treatment, such as physical and chemical methods, the dispersion of fly ash can be improved, thereby enhancing the strength and stability of the filling body. For example, the addition of activators can enhance the activity of fly ash, improve its dispersion in the filling material, and improve the strength of the filling body. At the same time, an appropriate amount of fly ash can improve the fluidity of the filling material, but an excessive amount may reduce the dispersibility of the slurry and affect the filling effect. Therefore, optimizing the use method and ratio of fly ash is crucial to improving its application effect in mining filling materials.
[0003] Research on mining filling materials usually focuses on their basic properties, such as compressive strength, initial setting time, final setting time, and slurry fluidity. However, there are relatively few studies on their performance under extreme environments, such as high and low temperature conditions. These extreme conditions place higher demands on the stability, durability, and thermodynamic properties of filling materials. For example, in high temperature environments, filling materials may experience thermal degradation, reducing their strength and toughness; while in low temperature environments, materials may become brittle and fragile, affecting their overall performance. In order to maintain the effectiveness of filling materials under these extreme conditions, researchers are exploring the use of modified fly ash to improve its performance. For example, by adding specific chemical additives or using special processing techniques, the dispersion of fly ash in filling materials can be improved, thereby improving its stability and strength under extreme temperatures. In addition, some studies are also focusing on how to optimize the thermal-performance and heat transfer process of the filling body through material design. For example, by adding phase change materials or using special gelling agents, the heat storage and release capacity of the filling material under high temperature conditions can be improved, thereby improving the comprehensive performance of the filling body. At the same time, by optimizing material formulation and construction technology, the application effect of filling materials under low temperature conditions can be improved, ensuring the safety and stability of mine filling.
[0004] In summary, the performance research of mining filling materials in extreme environments is an important research direction, which is of great significance to improving the safety and efficiency of mines. Through continuous research and technological innovation, high-performance filling materials that are more adaptable to extreme environments can be developed. Summary of the invention
[0005] The present invention aims to provide a modified fly ash-based mining filling material and its preparation method and application, so as to solve the problem of insufficient performance of mining filling materials in the prior art under extreme environments. The filling material is made of fly ash with specific modification, combined with lime, gypsum and sodium sulfate as a composite activator, which can not only maintain strength and stability in a high temperature environment and avoid structural damage caused by temperature increase, but also maintain its stable performance in a low temperature environment without excessive embrittlement or strength reduction, and is particularly suitable for mine filling applications.
[0006] The filling material of the present invention is based on modified fly ash, mixed with lime, cement, gypsum, sodium sulfate, epoxy resin and additives, and comprises, by weight: 40-80 parts of modified fly ash, 15-30 parts of lime, 30-50 parts of cement, 5-10 parts of gypsum, 3-8 parts of sodium sulfate, 5-10 parts of epoxy resin and 1-5 parts of additives.
[0007] The cement includes at least one of aluminate cement, sulphoaluminate cement, ferroaluminate cement and fluoroaluminate cement.
[0008] The gypsum includes at least one of plaster of Paris, phosphogypsum, desulfurized gypsum and fluorinated gypsum.
[0009] The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol A epoxy resin, and novolac epoxy resin.
[0010] The additive is at least one of a water reducer, a suspending agent, and a retarder. The retarder includes at least one of sodium gluconate, borax, or citric acid; the suspending agent includes at least one of sodium carboxymethyl cellulose, water-soluble polyvinyl alcohol, or hydroxypropyl methylcellulose; the water reducer includes at least one of a naphthalene-based water reducer, a melamine-based water reducer, or a polycarboxylic acid-based water reducer.
[0011] The preparation method of the modified fly ash of the present invention comprises the following steps:
[0012] Add fly ash into a high-speed mixer, add a nitrogen-containing silane coupling agent to obtain surface amino-modified fly ash, then add triethanolamine and organic acid and continue stirring to obtain modified fly ash. The amount of the nitrogen-containing silane coupling agent is 1-5% of the weight of the fly ash, and the amount of the triethanolamine and organic acid is 1-5% and 1-8% of the weight of the fly ash, respectively.
[0013] The nitrogen-containing silane coupling agent can be selected from at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, and di(3-trimethoxysilylpropyl)amine.
[0014] The organic acid is at least one of citric acid, tartaric acid, malic acid and succinic acid. The organic acid is preferably any two combinations of citric acid, tartaric acid and malic acid, and the mass ratio of the two organic acids is preferably 1:0.5-2.
[0015] The particle size distribution of fly ash is: D50 is 10-20μm, D90 is 50-100μm.
[0016] The present invention can effectively improve the compatibility of fly ash with materials such as cement, and improve its dispersibility and affinity in mining filling materials by using nitrogen silane coupling agent to modify the surface of fly ash. This modification not only enhances the surface activity of fly ash, but also helps to form a more uniform and stable filling material. Further secondary modification of fly ash using organic acid and triethanolamine can greatly improve the performance of the fly ash surface. These organic acids can react with the active points on the surface of fly ash to form stable chemical bonds, further improve the dispersibility of fly ash, reduce particle agglomeration, and enhance its binding force with materials such as cement. This dual modification method not only improves the mechanical properties of fly ash, but also enhances its stability under extreme temperature conditions, so that it can maintain good filling performance in both high and low temperature environments.
[0017] The nitrogen-containing silane coupling agent used in the present invention has higher reactivity and can form stable chemical bonds with the hydroxyl groups on the surface of fly ash. This bonding not only enhances the bonding strength of the interface, but also significantly improves the dispersibility of fly ash in the slurry, and can reduce agglomeration in both high and low temperature environments, thereby improving the overall performance of the filling material.
[0018] The present invention further prefers citric acid, tartaric acid, malic acid and succinic acid among the organic acids because they contain multiple carboxyl groups and shorter carbon chains, have stronger chemical activity, can better interact with fly ash, improve the dispersion performance of fly ash in the slurry, and further improve the filling performance.
[0019] The present invention also provides a method for preparing a modified fly ash-based mining filling material, comprising the following steps:
[0020] 40-80 parts of modified fly ash, 15-30 parts of lime, 30-50 parts of cement, 5-10 parts of gypsum, 3-8 parts of sodium sulfate, 5-10 parts of epoxy resin and 1-5 parts of additives are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0021] The present invention also provides an application of a modified fly ash-based mining filling material in mining filling, comprising mixing the filling material with water and adjusting the mass concentration of the slurry to 35-45% to meet the specific requirements of mine filling.
[0022] Lime is a key factor in stimulating the activity of fly ash due to its strong hydration properties. The OH- produced when lime dissolves in water provides an alkaline environment for the mixed system, which helps to destroy the Si-O and Al-O bonds in the fly ash glass. The participation of calcium ions further stimulates the activity of fly ash and promotes hydration to form cementitious products. These cementitious products are the main source of strength for mine filling materials. At the same time, the exothermic hydration reaction of lime promotes the reaction of the cementitious system, accelerates the thickening and hardening of the material, and improves the early strength, which is particularly important for application scenarios such as mine filling. In addition, the reaction products of lime and fly ash, such as hydrated calcium silicate and hydrated calcium aluminate, can form a dense structure, further enhancing the overall performance of the filling material.
[0023] As an effective chemical activator, sodium sulfate reacts with active silicates and aluminates in fly ash to generate new hydration products, such as calcium sulfate and calcium aluminum sulfate. These newly formed hydration products not only enhance the activity of fly ash, but also help improve the compressive strength and durability of the material. The addition of sodium sulfate promotes the activity of silicon and aluminum in fly ash, accelerates the hydration reaction, and generates more calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), which is the key to improving the strength of mining filling materials. In addition, the addition of sodium sulfate can also accelerate the hardening process of the material and improve its early strength, thereby speeding up construction and improving engineering efficiency.
[0024] As an activator, gypsum can accelerate the rate of hydration reaction in fly ash-cement paste. Its addition helps to adjust the alkalinity of the paste, thereby promoting the dissolution and hydration of silicate in fly ash. This process significantly enhances the activity of fly ash. At the same time, gypsum can also promote the hydration of tricalcium aluminate in cement and promote the formation of more calcium sulfonate. These calcium sulfonates not only provide crystal nuclei for the volcanic ash reaction of fly ash, but also accelerate the reaction process, thereby improving the overall strength.
[0025] The present invention adopts a composite activator of lime, gypsum and sodium sulfate, which effectively improves the activity of fly ash and optimizes its application in mining filling materials. This composite activator not only enhances the volcanic ash reaction of fly ash, but also maintains the stability of the filling material under high and low temperature environments, ensuring the filling effect and long-term stability of the material under extreme temperature conditions. Through the use of this activator, the technical effect of fly ash in mining filling materials has been significantly improved, which is of great significance for the stable mining of mines and environmental protection.
[0026] The epoxy resin used in the present invention plays a key role in mine filling materials due to its excellent bonding properties. It can effectively bond materials such as fly ash and cement into a filling body with certain strength and stability. During the curing process, the volume shrinkage of the epoxy resin is extremely small, which helps to reduce the internal stress and deformation of the cured material, thereby ensuring the stability of the filling body. The cured epoxy resin forms a hard solid, providing effective support for the surrounding rock of the mine and reducing the risk of collapse in the goaf. In addition, the chemical stability of the epoxy resin enables it to maintain its performance unaffected in the mine environment even in the face of corrosive substances such as moisture, acids and alkalis, thereby improving the durability of the filling body. The curing of the epoxy resin does not rely on high temperature and can be carried out at room temperature or low temperature, so that it can play a role in mines under different environmental conditions, providing a strong guarantee for mine safety.
[0027] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0028] 1) The present invention uses a composite system of nitrogen-containing silane coupling agent, triethanolamine and organic acid to modify fly ash, which not only improves the dispersibility of fly ash in slurry, but also significantly enhances its filling performance. Especially under extreme temperature conditions, the modified fly ash can maintain excellent filling effect and long-term stability, which is crucial for applications in special environments such as mines. Through this composite modification technology, the volcanic ash activity of fly ash is fully utilized, and at the same time, it also provides a strong guarantee for the durability and stability of the filling material.
[0029] 2) The present invention effectively enhances the activity of fly ash by mixing lime, gypsum and sodium sulfate as activators, ensuring that the filling material exhibits good stability under both high and low temperature conditions, thereby achieving excellent technical performance in applications such as mine filling.
[0030] 3) The epoxy resin used in the present invention has good bonding properties and can effectively bond materials such as fly ash and cement into a filling body with certain strength and stability. The volume shrinkage of the epoxy resin is extremely small, which reduces the internal stress and deformation of the material after curing, thereby ensuring the stability of the filling body. The chemical stability of the epoxy resin can keep its performance unaffected even in the face of corrosive substances such as moisture, acid and alkali, thereby improving the durability of the filling body.
[0031] 4) The raw materials such as fly ash, lime and phosphogypsum used in the present invention are widely available and inexpensive, and only simple mixing and stirring is required at the construction site to quickly prepare the required filling material. This method greatly simplifies the on-site operation steps, while significantly reducing production costs and improving construction efficiency. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below by specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0033] Experimental Materials:
[0034] The particle size distribution of fly ash used in the present invention is: D50 is 20μm, D90 is 80μm. The main chemical component is SiO2, accounting for up to 45.85%, and it also contains a small amount of Al2O3, Fe2O3, and CaO. The specific composition is as follows:
[0035] Table 1 Chemical composition of fly ash (wt / %)
[0036]
[0037] Lime, gypsum, cement, sodium sulfate, additives, etc. are all commercially available.
[0038] Example 1
[0039] The present embodiment provides a modified fly ash-based mining filling material, the formula of which is: 40 parts of modified fly ash, 30 parts of lime, 50 parts of Portland cement, 10 parts of desulfurized gypsum, 4 parts of sodium sulfate, 5 parts of bisphenol A epoxy resin, 1 part of sodium carboxymethyl cellulose, and 1 part of polycarboxylic acid water reducer.
[0040] The preparation method of modified fly ash comprises the following steps:
[0041] Add fly ash to a high-speed mixer, adjust the mixer speed to 600r / min, the temperature to 80°C, add γ-aminopropyltrimethoxysilane, continue stirring for 30 minutes to obtain surface-aminated fly ash, then add triethanolamine and citric acid and continue stirring for 30 minutes, cool to room temperature, and obtain modified fly ash. The amount of γ-aminopropyltrimethoxysilane is 1% of the weight of the fly ash, and the amounts of triethanolamine and organic acid are 2% and 3% of the weight of the fly ash, respectively.
[0042] The method for preparing the modified fly ash-based mining filling material of this embodiment comprises the following steps:
[0043] 40 parts of modified fly ash, 30 parts of lime, 50 parts of Portland cement, 10 parts of desulfurized gypsum, 4 parts of sodium sulfate, 5 parts of bisphenol A epoxy resin, 1 part of sodium carboxymethyl cellulose and 1 part of polycarboxylic acid water reducer are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0044] Example 2
[0045] The present embodiment provides a modified fly ash-based mining filling material, the formula of which is: 70 parts of modified fly ash, 15 parts of lime, 40 parts of sulphoaluminate cement, 7 parts of phosphogypsum, 6 parts of sodium sulfate, 7 parts of bisphenol F epoxy resin, 1 part of sodium gluconate, and 1 part of polycarboxylic acid water reducer.
[0046] The preparation method of modified fly ash comprises the following steps:
[0047] Add fly ash to a high-speed mixer, adjust the mixer speed to 700r / min, the temperature to 85°C, add N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, continue stirring for 40 minutes to obtain surface-aminated fly ash, then add triethanolamine and tartaric acid and continue stirring for 30 minutes, cool to room temperature, and obtain modified fly ash. The amount of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 1.5% of the weight of the fly ash, and the amounts of triethanolamine and tartaric acid are 1% and 4% of the weight of the fly ash, respectively.
[0048] The method for preparing the modified fly ash-based mining filling material of this embodiment comprises the following steps:
[0049] 70 parts of modified fly ash, 15 parts of lime, 40 parts of sulphoaluminate cement, 7 parts of phosphogypsum, 6 parts of sodium sulfate, 7 parts of bisphenol F epoxy resin, 1 part of sodium gluconate and 1 part of polycarboxylic acid water reducer are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0050] Example 3
[0051] The present embodiment provides a modified fly ash-based mining filling material, the formula of which is: 60 parts of modified fly ash, 20 parts of lime, 30 parts of ferroaluminate cement, 5 parts of gypsum, 8 parts of sodium sulfate, 8 parts of bisphenol F epoxy resin, 1 part of borax, and 1 part of melamine water reducer.
[0052] The preparation method of modified fly ash comprises the following steps:
[0053] Add fly ash to a high-speed mixer, adjust the mixer speed to 750r / min, the temperature to 85°C, add N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, continue stirring for 45 minutes to obtain surface-aminated fly ash, then add triethanolamine and malic acid and continue stirring for 40 minutes, cool to room temperature, and obtain modified fly ash. The amount of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane is 4% of the weight of the fly ash, and the amounts of triethanolamine and malic acid are 3% and 2% of the weight of the fly ash, respectively.
[0054] The method for preparing the modified fly ash-based mining filling material of this embodiment comprises the following steps:
[0055] 60 parts of modified fly ash, 20 parts of lime, 30 parts of ferroaluminate cement, 5 parts of gypsum, 8 parts of sodium sulfate, 8 parts of bisphenol F epoxy resin, 1 part of borax and 1 part of melamine water reducer are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0056] Example 4
[0057] The present embodiment provides a modified fly ash-based mining filling material, the formula of which is: 80 parts of modified fly ash, 15 parts of lime, 35 parts of fluoroaluminate cement, 10 parts of fluorgypsum, 6 parts of sodium sulfate, 10 parts of phenolic epoxy resin, 1 part of borax, and 2 parts of polycarboxylic acid water reducer.
[0058] The preparation method of modified fly ash comprises the following steps:
[0059] Add fly ash into a high-speed mixer, adjust the mixer speed to 750r / min, the temperature to 80°C, add N-aminoethyl-3-aminopropylmethyldimethoxysilane, continue stirring for 45 minutes to obtain surface-aminated fly ash, then add triethanolamine and succinic acid and continue stirring for 40 minutes, cool to room temperature, and obtain modified fly ash. The amount of N-aminoethyl-3-aminopropylmethyldimethoxysilane is 5% of the weight of the fly ash, and the amounts of triethanolamine and succinic acid are 1.5% and 1.5% of the weight of the fly ash, respectively.
[0060] The method for preparing the modified fly ash-based mining filling material of this embodiment comprises the following steps:
[0061] 80 parts of modified fly ash, 15 parts of lime, 35 parts of fluoroaluminate cement, 10 parts of fluorgypsum, 6 parts of sodium sulfate, 10 parts of phenolic epoxy resin, 1 part of borax and 2 parts of polycarboxylic acid water reducer are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0062] Example 5
[0063] The present embodiment provides a modified fly ash-based mining filling material, the formula of which is: 55 parts of modified fly ash, 25 parts of lime, 40 parts of Portland cement, 9 parts of desulfurized gypsum, 4 parts of sodium sulfate, 7 parts of bisphenol A epoxy resin, 2 parts of borax, and 1 part of polycarboxylic acid water reducer.
[0064] The preparation method of modified fly ash comprises the following steps:
[0065] Add fly ash to a high-speed mixer, adjust the mixer speed to 750r / min, the temperature to 80°C, add di(3-trimethoxysilylpropyl)amine and γ-aminopropyltrimethoxysilane mixed coupling agent, continue stirring for 45 minutes to obtain surface amino fly ash, then add triethanolamine and citric acid and continue stirring for 40 minutes, cool to room temperature, and obtain modified fly ash. The amount of di(3-trimethoxysilylpropyl)amine and γ-aminopropyltrimethoxysilane is 1% and 2% of the weight of the fly ash, respectively, and the amount of triethanolamine and citric acid is 3% and 3.5% of the weight of the fly ash, respectively.
[0066] The method for preparing the modified fly ash-based mining filling material of this embodiment comprises the following steps:
[0067] 55 parts of modified fly ash, 25 parts of lime, 40 parts of Portland cement, 9 parts of desulfurized gypsum, 4 parts of sodium sulfate, 7 parts of bisphenol A epoxy resin, 2 parts of borax and 1 part of polycarboxylic acid water reducer are stirred and mixed uniformly to obtain the modified fly ash mine filling material.
[0068] Example 6
[0069] Citric acid and tartaric acid were used in a ratio of 1:2 to replace the citric acid in Example 1, and other conditions were the same as those in Example 1.
[0070] Example 7
[0071] Citric acid and malic acid were used in a 1:1 ratio to replace the citric acid in Example 1. Other conditions were the same as those in Example 1.
[0072] Example 8
[0073] Tartaric acid and malic acid were used in a ratio of 2:1 to replace the citric acid in Example 1, and other conditions were the same as in Example 1.
[0074] Example 9
[0075] N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane were used in a 1:1 ratio to replace the γ-aminopropyltrimethoxysilane in Example 1. Other conditions were the same as in Example 1.
[0076] Example 10
[0077] γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane were used in a 2:1 ratio to replace the γ-aminopropyltrimethoxysilane in Example 1. Other conditions were the same as in Example 1.
[0078] Embodiment 11
[0079] N-aminoethyl-3-aminopropylmethyldimethoxysilane and bis(3-trimethoxysilylpropyl)amine were used in a 1:1 ratio to replace the γ-aminopropyltrimethoxysilane in Example 1. Other conditions were the same as those in Example 1.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that the fly ash is not modified, and other conditions are the same as those in Example 1.
[0082] Comparative Example 2
[0083] The difference from Example 1 is that the step of modifying the fly ash with γ-aminopropyltrimethoxysilane is omitted, and only triethanolamine and citric acid are used to modify the fly ash. Other conditions are the same as those in Example 1.
[0084] Comparative Example 3
[0085] The difference from Example 1 is that the steps of modifying fly ash with triethanolamine and citric acid are omitted, and only γ-aminopropyltrimethoxysilane is used to modify fly ash. Other conditions are the same as those in Example 1.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that stearic acid is used instead of citric acid, and other conditions are the same as those in Example 1.
[0088] Comparative Example 5
[0089] The difference from Example 1 is that γ-methacryloxypropyltrimethoxysilane (KH570) is used instead of γ-aminopropyltrimethoxysilane, and other conditions are the same as those in Example 1.
[0090] Comparative Example 6
[0091] The difference from Example 1 is that no lime is added, an equal amount of modified fly ash is used instead of lime, and other conditions are the same as those in Example 1.
[0092] Comparative Example 7
[0093] The difference from Example 1 is that no gypsum is added, an equal amount of modified fly ash is used instead of gypsum, and other conditions are the same as those in Example 1.
[0094] Comparative Example 8
[0095] The difference from Example 1 is that no sodium sulfate is added, an equal amount of modified fly ash is used instead of sodium sulfate, and other conditions are the same as those in Example 1.
[0096] Comparative Example 9
[0097] The difference from Example 1 is that no epoxy resin is added, an equal amount of modified fly ash is used instead of the epoxy resin, and other conditions are the same as those in Example 1.
[0098] The properties of the modified fly ash mining filling materials prepared in this embodiment and the comparative example are shown in Table 1. The stirred slurry was injected into a 40mm×40mm×160mm triple mold, and after curing at room temperature of 25°C, the material was demoulded and cut, and the compressive strength of the material was tested after the material was dried.
[0099] Retention rate of compressive strength against water penetration: Take the sample cured for 60 days and test the compressive strength, recorded as M1. Then soak the sample in water for 4 days, and test the compressive strength after drying, recorded as M2. The retention rate of compressive strength = M2 / M1*100.
[0100] Heat resistance test: The water loss temperature of calcium sulfonate is about 80℃~90℃. To simulate the extreme high temperature environment in the mine, the filling specimens were placed under the condition of 60℃ water bath temperature for simulation test. The specific method is: set the water bath temperature to 60℃, and put the 60d curing specimens on the water bath tray to ensure that the specimens are not in contact with water. The water bath time is set to 7d and 28d, and the specimens are taken out of the water bath for compressive strength test. The compressive strength of the specimens before the water bath is recorded as A1, and the compressive strength of the specimens after the water bath treatment is recorded as A2. The 60℃ compressive strength retention rate = A2 / A1*100. Take 10 specimens in each group and take the average value of the 10 groups of experiments.
[0101] Antifreeze performance test: The specific method is: put the sample that has been cured for 60 days into a constant temperature box and place it at 30℃ for 12 hours, then adjust the constant temperature box to 0℃ and place it for 12 hours, simulating the antifreeze performance of the filling material under extreme environment (such as large temperature difference between day and night), and take out the sample at 7d and 28d for compressive strength test. The compressive strength of the sample before treatment is recorded as B1, and the compressive strength of the sample after treatment is recorded as B2. The 0℃ compressive strength retention rate = B2 / B1*100. Take 10 samples in each group and take the average value of the 10 groups of experiments.
[0102] The compressive strength is tested using JC / T984-2011; the vertical expansion rate refers to Appendix C of GB 50119-2003.
[0103] Table 1 Filling material properties of different embodiments and control examples
[0104]
[0105]
[0106] According to the data in Performance Test Table 1, the modified fly ash mining filling material prepared by the present invention exhibits excellent heat resistance and cold resistance in both high and low temperature environments, with a compressive strength retention rate of more than 96%, and an expansion rate controlled below 3.5%. This modified fly ash exhibits good dispersibility in the slurry, thanks to the use of a mixed activator of lime, gypsum and sodium sulfate, which together significantly enhance the activity of the fly ash. Therefore, the filling material can still maintain stability under extreme temperature conditions and has good water resistance, making it very suitable for filling operations in mining environments.
[0107] By comparing Example 1 with Examples 6-8, it can be found that the use of a mixed organic acid of any two of citric acid, malic acid and tartaric acid as a modifier can significantly improve the heat resistance, cold resistance and water resistance of the modified fly ash filling material compared to a single organic acid, and the shrinkage rate is also lower. In addition, by comparing Example 1 with Examples 9-11, the results show that the use of two coupling agents such as γ-aminopropyltrimethoxysilane, N (β-aminoethyl) γ-aminopropyltrimethoxysilane, N (β-aminoethyl) γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, and di (3-trimethoxysilylpropyl) amine can also better enhance the heat resistance, cold resistance and water resistance of the filling material compared to a single coupling agent.
[0108] From the comparative analysis of Example 1 and Comparative Examples 1-3, it can be found that the fly ash in Comparative Example 1 was not subjected to any modification treatment, the fly ash in Comparative Example 2 was modified only by triethanolamine and citric acid, and the fly ash in Comparative Example 3 was modified only by a silane coupling agent. Compared with Example 1, the filling materials of Comparative Examples 1-3 had little difference in compressive strength within 28 days, but showed obvious deficiencies in heat resistance, cold resistance and water resistance. This performance difference may be due to the poor dispersibility of the fly ash in the slurry in Comparative Examples 1-3.
[0109] By comparing the test results of Example 1 with Comparative Examples 4-5, it can be seen that stearic acid is used to replace citric acid in Comparative Example 4, while nitrogen-free silane coupling agent KH570 is used in Comparative Example 5 to modify fly ash. Experimental data show that the filling materials of Comparative Examples 4-5 are not as good as those of Example 1 in terms of heat resistance, cold resistance and water resistance. This difference in performance may be due to the higher reactivity provided by the polyhydroxy structure of citric acid, and the more effective interaction between the nitrogen-containing silane coupling agent and fly ash, thereby enhancing the modification effect of fly ash. Therefore, the selection of the modifier is crucial to improving the comprehensive performance of the filling material.
[0110] In the study of comparing Example 1 with Comparative Examples 6-8, we found that the filling materials of Comparative Example 6 omitting lime, Comparative Example 7 omitting gypsum, and Comparative Example 8 omitting sodium sulfate were obviously inferior to those of Example 1 in terms of heat resistance, cold resistance, and water resistance. This shows that the combination of lime, gypsum, and sodium sulfate as activators is crucial to improving the activity of fly ash, and their combined effect can effectively improve the stability of the filling material under different environments, especially the performance under high and low temperature conditions. Therefore, the synergistic effect of these three substances plays a key role in the modification of fly ash filling materials.
[0111] When comparing the test results of Example 1 with Comparative Example 9, when the epoxy resin is omitted, the cold and heat resistance of the filling material of Comparative Example 9 is not much different from that of Example 1. However, the water penetration resistance and shrinkage rate of Comparative Example 9 are obviously inferior to those of Example 1. This may be because the omission of the epoxy resin weakens the adhesion between the materials, and the internal stress and deformation of the material after curing increase, thereby affecting the overall stability of the filling body.
[0112] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A modified fly ash-based mining filling material, characterized in that: The filling material comprises the following components in parts by weight: 40-80 parts of modified fly ash, 15-30 parts of lime, 30-50 parts of cement, 5-10 parts of gypsum, 3-8 parts of sodium sulfate, 5-10 parts of epoxy resin, and 1-5 parts of additives; The modified fly ash is prepared by the following steps: Add fly ash into a high-speed mixer, add a nitrogen-containing silane coupling agent to obtain fly ash with surface amino, then add triethanolamine and an organic acid and continue stirring to obtain modified fly ash, wherein the amount of the nitrogen-containing silane coupling agent is 1-5% of the weight of the fly ash, and the amounts of the triethanolamine and the organic acid are 1-5% and 1-8% of the weight of the fly ash respectively; The nitrogen-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, and bis(3-trimethoxysilylpropyl)amine; The organic acid is at least one of citric acid, tartaric acid, malic acid and succinic acid.
2. The filling material according to claim 1, characterized in that The cement includes at least one of aluminate cement, sulphoaluminate cement, ferroaluminate cement and fluoroaluminate cement.
3. The filling material according to claim 1, characterized in that The gypsum includes at least one of plaster of Paris, phosphogypsum, desulfurized gypsum and fluorinated gypsum.
4. The filling material according to claim 1, characterized in that The epoxy resin includes at least one of bisphenol A epoxy resin and novolac epoxy resin.
5. The filling material according to claim 1, characterized in that The additive is at least one of a water reducing agent, a suspending agent and a retarder.
6. The filling material according to claim 5, characterized in that The retarder includes at least one of sodium gluconate, borax or citric acid; the suspending agent includes at least one of sodium carboxymethyl cellulose, water-soluble polyvinyl alcohol or hydroxypropyl methylcellulose; the water reducer includes at least one of naphthalene-based water reducer, melamine-based water reducer or polycarboxylic acid-based water reducer.
7. The method for preparing the modified fly ash-based mining filling material according to any one of claims 1 to 6, characterized in that: 40-80 parts of modified fly ash, 15-30 parts of lime, 30-50 parts of cement, 5-10 parts of gypsum, 3-8 parts of sodium sulfate, 5-10 parts of epoxy resin and 1-5 parts of additives are stirred and mixed uniformly to obtain the modified fly ash mining filling material.
8. The use of the modified fly ash-based mining filling material according to any one of claims 1 to 6 in mining filling, characterized in that: The method comprises mixing the filling material with water and adjusting the mass concentration of the slurry to 35-45%.
Citation Information
Patent Citations
Double-doped grouting material for repairing pavement and preparation method of double-doped grouting material
CN107840626A
Inorganic solidified fly ash filling material and preparation method thereof
CN109400080A
Concrete reinforcing and toughening agent and preparation method thereof
CN113135690A